Proposta construtivista em questão: analise da experiencia brasileira no ensino da leitura e escrita - Moura, Josana Ferreira Bassi de [UNESP]; Dongo-Montoya, Adrian Oscar [UNESP] (My University, 2012)
Years after the constructivism theory was adopted by “Parameters for National Syllabuses”, the results have pointed to a worse performance in teaching and learning with regards to reading and writing. This article presents the conclusions proceeding from investigation about the probable reasons for the student’s lack of success in reading and writing, and its relation to Emília Ferreiro’s constructivism proposals. Interviews were made as well as sit in class observation were done, with twenty teachers at six Fundamental Level 1 schools in Ourinhos, SP State, in schools that had been awarded the best and the worst performance rating in the Prova Brasil-2005, with this objective: to know and analyze the teacher’s conceptions under their practices and their practices in the classes. The conclusion is: it is not possible to attribute the students’ lack of success in reading and writing; these studies showed that many teachers, most of them, have a non-constructivist concept of teaching and learning, it means that they do not apply Ferreiro’s researches.

Tantos anos depois da adoção da teoria construtivista pelos Parâmetros Curriculares Nacionais, persiste o insucesso dos alunos na aprendizagem da leitura e da escrita. Este artigo apresenta resultados provenientes de investigação, realizada para procurar compreender as prováveis razões do insucesso dos alunos em leitura e escrita e sua relação com a proposta construtivista de Emília Ferreiro. Foram feitas entrevistas e sessões de observação de sala de aula, com 20 professores do Ensino Fundamental I, de seis escolas municipais da cidade de Ourinhos, com melhor ou pior desempenho na Prova Brasil 2005. O objetivo foi conhecer e analisar a concepção teórica subjacente às práticas, e as próprias práticas adotadas para o ensino e a aprendizagem da leitura e da escrita. Descobriu-se que não é possível atribuir-se o fracasso à adoção dos pressupostos construtivistas, visto que a maioria dos professores possui uma concepção não construtivista de ensino e de aprendizagem e não se apoia, de fato, nas pesquisas de Ferreiro.
The constructivist proposal to reading/writing in question: analysis of Brazilian experience
Keywords: Psicologia Genética; Ensino da escrita e leitura; Proposta construtivista